Efavirenz, Tenofovir and Emtricitabine Combined with First-Line Tuberculosis Treatment in Tuberculosis–Hiv-Coinfected Tanzanian Patients: A Pharmacokinetic and Safety Study. Issue 1 (January 2013) - Semvua, Hadija H; Mtabho, Charles M; Fillekes, Quirine; Van Den Boogaard, Jossy; Kisonga, Riziki M; Mleoh, Liberate; Ndaro, Arnold; Kisanga, Elton R; Van Der Ven, Andre; Aarnoutse, Rob E; Kibiki, Gibson S; Boeree, Martin J; et al.
Background: To evaluate the effect of rifampicin-based tuberculosis (TB) treatment on the pharmacokinetics of efavirenz/tenofovir/emtricitabine in a fixed-dose combination tablet, and vice versa, in Tanzanian TB–HIV-coinfected patients. Methods: This was a Phase II open-label multiple dose pharmacokinetic and safety study. This study was conducted in TB–HIV-coinfected Tanzanian patients who started TB treatment (rifampicin/isoniazid/pyrazinamide/ethambutol) at week 1 to week 8 and continued with rifampicin and isoniazid for another 16 weeks. Antiretroviral treatment (ART) of efavirenz/tenofovir/emtricitabine in a fixed-dose combination tablet was started at week 4 after initiation of TB treatment. A 24-h pharmacokinetic sampling curve was recorded at week 8 (with TB treatment) and week 28 (ART alone). For TB drugs, blood samples at 2 and 5 h post-dose were taken at week 3 (TB treatment alone) and week 8 (with ART). Results: A total of 25 patients (56% male) completed the study; 21 had evaluable pharmacokinetic profiles. The area under the concentration–time curve 0–24 h post-dose of efavirenz, tenofovir and emtricitabine were slightly higher when these drugs were coadministered with TB drugs; geometric mean ratios (90% CI) were 1.08 (0.90, 1.30), 1.13 (0.93, 1.38) and 1.05 (0.85, 1.29), respectively. For TB drugs, equivalence was suggested for peak plasma concentrations when administered with and without efavirenz/tenofovir/emtricitabine. Adverse events were mostly mild and no serious adverse events or drug discontinuations were reported. Conclusions: Coadministration of efavirenz, tenofovir and emtricitabine with a standard first-line TB treatment regimen did not significantly alter the pharmacokinetic parameters of these drugs and was tolerated well by Tanzanian TB patients who are coinfected with HIV.